Physical characterization of Titanium Dioxide based varistor materials doped with Cobalt Oxide - Kothandapani Z.; Begum S.; Nainar M.A.M.; Gholizadeh S.; Yee W.M. (2023)
TiO2 varistor material acts as surge arrestors against transient voltages in electrical and electronic equipments. However, the enhancement of properties as a surge protector is very much dependent on the types of dopants being used. Not only that, the microstructure and enhanced mechanical characteristics is anticipated to improve the surge characteristics. In this investigation, the effect of Cobalt Oxide (Co3O4) on Titanium Dioxide (TiO2) was investigated. The percent of dopant was varied at various levels and the prepared samples were characterized by evaluating the physical properties like green density, fired density, sintered strength, axial and radial shrinkage, average grain size and microstructure. A comparison between doped and undoped TiO2 was also made. The physical, mechanical and microstructure were improved for doped TiO2 samples and it was highest for the samples prepared from powder with 98.5 % TiO2.1.5% Co3O4 and sintered at 1350C. 2012 IEEE.